AnNaqlu car financing-i: A study on Al-Ijarah Thumma Al-Bai (AITAB) selection among customers of Bank Rakyat Putrajaya / Muhammad Noor Ridzuan Idris and Muhammad Ashraf Mahadzir - Idris, Muhammad Noor Ridzuan; Mahadzir, Muhammad Ashraf (2014)
Vehicle is a must as people used it to perform their daily responsibilities and activities. In owning a car people will apply for car financing and their choice will be of either conventional hire purchase or islamic hire purchase from banking institution. According to the data obtained through BKRM’s annual report from 2010 – 2012, their figure of disbursement on AITAB are quite wobbly. The total disbursement for that three consecutive years starting from 2010 – 2012 is RM10,330,000, RM639,759,000 and RM413,206,000 respectively. This paper presents the factors affecting the selection of AnNaqlu car financing that uses the concept of Al-Ijarah Thumma Al-Bay (AiTAB) among Bank Rakyat Putrajaya customers. The study is confined to Islamic hire purchase of bank rakyat only in Putrajaya. The objective of this paper is to determined the relationship between adherence to shariah, financial counseling available, car dealer relationship and profit rate with AiTAB’s selection among customers. Descriptive research, quantitative research and causal research have been used to conduct this study. The finding was gained through questionnaires distributed to 150 customers. All 150 of distributed questionnaires were managed to be usable and valid for the further analysis of data. The findings indicated that adherence to shariah, financial counseling available, car dealer relationship and profit rate were found to be significant